The Ideology Of Madihin Arts In Banjarmasin: Henry Giroux's Conservative Ideological Perspective - Muhammad Budi Zakia Sani; Wadiyo Wadiyo; Suminto A. Sayuti; Syakir Syakir (Universitas Negeri Semarang, 2023)
Madihin is a traditional art in the Banjar community which is a local wisdom identity owned by the Banjar people. The background of this research is how a concept and ideology about art certainly becomes the basis or main basis for artists in believing in and carrying out the process of art. The methodology used in this paper is a qualitative approach by looking at and approaching the object of research naturally and naturally. The results and discussion obtained in this study are how a thought or ideology that is owned by madihin artists in the city of Banjarmasin is the ideology put forward by Henry Giroux, namely conservative ideology as a form of preservation and maintaining traditional values contained in madihin art.